A PRÁTICA COMPARATISTA EM O FALSO MENTIROSO: MEMÓRIAS, DE SILVIANO SANTIAGO - Perizzolo, Gabriela (Organon, 2004)
The objective of this paper is to study some of the Silviano Santiago’s critical essays - those oneswhere ideas related to the comparative activity is discussed – establishing a relation with his novel O falsomentiroso: memórias. Trough out this parallel, we intend to emphasize a very important aspect considered byComparative Literature: the value of the differences